Corporate Social Responsibility and Internal Control Effectiveness1. (29th April 2017) - Kim, Young Sang; Kim, Yura; Kim, Hyun‐Dong
Abstract: This study empirically examines whether corporate social responsible firms exhibit more effective internal control over financial reporting. Specifically, we investigate whether socially responsible firms apply business practices to ensure financial transparency and accountability for their stakeholders. Using various measures of corporate social responsibility (CSR) and a battery of robust regression analysis over the period from 2004 to 2012, we find that CSR firms are more likely to have effective internal control under Section 404 of the Sarbanes‐Oxley Act (SOX). Our results are robust to the propensity matching of firm characteristics, considering various measures of CSR, and adjusting for several endogenous problems.